2004
DOI: 10.1097/00001756-200405190-00008
|View full text |Cite
|
Sign up to set email alerts
|

Delayed neurotrophin treatment supports auditory neuron survival in deaf guinea pigs

Abstract: As key factors in the development and maintenance of the auditory system, neurotrophins can prevent auditory neuron degeneration when applied within three to five days of deafening. We tested each of the neurotrophins BDNF, NT-3, NT-4/5 and NGF for their ability to support auditory neuron survival following a two-week period of deafness in guinea pigs, when approximately 15% auditory neuron degeneration has already occurred. Although delayed, the treatment with each neurotrophin prevented further degeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 18 publications
(20 reference statements)
9
70
1
4
Order By: Relevance
“…Neurotrophins have been shown, by this study and others, to act as survival factors for mature SGNs in animal models of SNHL (12)(13)(14)(15). Other research has demonstrated that neurotrophins and electrical stimulation act in synergy to prevent SGN degeneration (25,21).…”
Section: Safety and Clinical Implicationssupporting
confidence: 52%
See 1 more Smart Citation
“…Neurotrophins have been shown, by this study and others, to act as survival factors for mature SGNs in animal models of SNHL (12)(13)(14)(15). Other research has demonstrated that neurotrophins and electrical stimulation act in synergy to prevent SGN degeneration (25,21).…”
Section: Safety and Clinical Implicationssupporting
confidence: 52%
“…Moreover, these neurotrophins are also thought to contribute to neuronal maintenance in the adult inner ear (5). In the absence of hair cells, the neuroprotective effects of chronically delivered exogenous BDNF or NT-3 on SGNs in vivo has been demonstrated (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Six of these animals then received BDNF treatment and six received Ringer's solution to serve as deafened controls. BDNF was chosen because it has been shown to improve SGN survival after deafness in several studies in the guinea pig (Staecker et al 1996;Miller et al 1997;Gillespie et al 2004;Shepherd et al 2005;Agterberg et al 2008) and this was a requirement of the validation of the round window delivery method developed here. Furthermore, BDNF has been the most extensively examined neurotrophin for potential use with cochlear implants Song et al 2009); thus, it seemed appropriate to begin our investigations in hearing animals with this protein.…”
Section: Experimental Subjects and Designmentioning
confidence: 99%
“…Fluid was then manually pushed through the delivery system with a syringe to test its patency in situ. Cochleae were then removed and SGN density was assessed to establish whether our delivery method resulted in the usual protection of SGNs observed with BDNF treatment (Staecker et al 1996;Miller et al 1997;Gillespie et al 2004;Shepherd et al 2005;Wise et al 2005;Agterberg et al 2008;Havenith et al 2011).…”
Section: Experimental Subjects and Designmentioning
confidence: 99%
See 1 more Smart Citation